2015
DOI: 10.1371/journal.pone.0120745
|View full text |Cite
|
Sign up to set email alerts
|

Hybridization of Two Major Termite Invaders as a Consequence of Human Activity

Abstract: While hybridization of an invasive species with a native species is a common occurrence, hybridization between two invasive species is rare. Formosan subterranean termites (Coptotermes formosanus) and Asian subterranean termites (C. gestroi) are both ecologically successful and are the two most economically important termite pests in the world. Both species have spread throughout many areas of the world due to human activity; however, their distributions overlap in only three narrow areas because of distinct e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
69
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(72 citation statements)
references
References 60 publications
1
69
2
Order By: Relevance
“…Alate collection records up until then showed that C. gestroi alates swarmed from February to mid-April and C. formosanus alates from mid-April to June. In fact, according to Scheffrahn [25], “…as soon as C. formosanus begins its first flights, those of C. gestroi cease…” In 2013, however, Chouvenc et al [8] observed two events of simultaneous flights by these two species in Broward County. A more thorough survey carried out in 2014 at the same location revealed that C. gestroi alates swarmed from late February to early June, while C. formosanus swarmed from mid-March to mid-June.…”
Section: Sympatric Areasmentioning
confidence: 99%
See 2 more Smart Citations
“…Alate collection records up until then showed that C. gestroi alates swarmed from February to mid-April and C. formosanus alates from mid-April to June. In fact, according to Scheffrahn [25], “…as soon as C. formosanus begins its first flights, those of C. gestroi cease…” In 2013, however, Chouvenc et al [8] observed two events of simultaneous flights by these two species in Broward County. A more thorough survey carried out in 2014 at the same location revealed that C. gestroi alates swarmed from late February to early June, while C. formosanus swarmed from mid-March to mid-June.…”
Section: Sympatric Areasmentioning
confidence: 99%
“…A more thorough survey carried out in 2014 at the same location revealed that C. gestroi alates swarmed from late February to early June, while C. formosanus swarmed from mid-March to mid-June. Alates of these two species swarmed on the same nights 24 times between 18 March and 9 June, with five events of major simultaneous swarming, i.e., >100 alates of both species collected from a light trap [8]. …”
Section: Sympatric Areasmentioning
confidence: 99%
See 1 more Smart Citation
“…Two species, C. formosanus and C. gestroi, are particularly invasive (Chouvenc et al 2015a) and have spread far beyond their native range with the help of human maritime activity (Scheffrahn & Crowe 2011;Rust & Su 2012). They contribute in large part to the annual $40 billion cost associated with termite damage and control around the world (Rust & Su 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, both species have spread extensively and, with the help of human activity, have established sympatrically within non-native climatic boundaries (Chouvenc et al 2015a) including southern Taiwan, Hainan (China), Oahu (Hawaii), and the metropolitan area of southeastern Florida (Chouvenc et al 2015a; Fig. 1).…”
Section: Introductionmentioning
confidence: 99%